2009
DOI: 10.1371/journal.ppat.1000494
|View full text |Cite
|
Sign up to set email alerts
|

iNOS-Producing Inflammatory Dendritic Cells Constitute the Major Infected Cell Type during the Chronic Leishmania major Infection Phase of C57BL/6 Resistant Mice

Abstract: Leishmania major parasites reside and multiply in late endosomal compartments of host phagocytic cells. Immune control of Leishmania growth absolutely requires expression of inducible Nitric Oxide Synthase (iNOS/NOS2) and subsequent production of NO. Here, we show that CD11b+ CD11c+ Ly-6C+ MHC-II+ cells are the main iNOS-producing cells in the footpad lesion and in the draining lymph node of Leishmania major-infected C57BL/6 mice. These cells are phenotypically similar to iNOS-producing inflammatory DC (iNOS-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
171
2
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(189 citation statements)
references
References 46 publications
12
171
2
4
Order By: Relevance
“…The chemokine receptor CCR2 has been implicated in the recruitment of inflammatory monocytes during infection (40). CCR2 deficiency impaired development of a protective immune response in several infectious models (40,59,60). We observed that CCR2 deficiency had no impact on the course of Brucella infection in the lungs, liver, or spleen at all time points tested.…”
Section: Discussionmentioning
confidence: 58%
“…The chemokine receptor CCR2 has been implicated in the recruitment of inflammatory monocytes during infection (40). CCR2 deficiency impaired development of a protective immune response in several infectious models (40,59,60). We observed that CCR2 deficiency had no impact on the course of Brucella infection in the lungs, liver, or spleen at all time points tested.…”
Section: Discussionmentioning
confidence: 58%
“…We observed that parasite replication in the footpad of B-IL-4 −/− and IL-4 −/− chimeras was controlled to a greater degree than in the LN compared with μMT B-WT chimeras. The footpad has a higher frequency of iNOS-secreting macrophages and DCs to host parasites than the LN and is capable of killing intracellular parasites (25,27), which might account for a slower but effective control in the LN. This was further accompanied by strikingly reduced detrimental type 2 antibody (Fig.…”
Section: Cd3mentioning
confidence: 99%
“…Après cette description initiale, de nombreuses études ont montré chez la souris l'existence d'une population cellulaire comparable dans de nombreux cas d'inflammation causée par des pathogènes, qu'il s'agisse de bactéries (Listeria monocytogenes, Streptococcus pneumoniae, Salmonella typhimurium, etc.) [4][5][6], virus (virus de l'herpès, virus de la grippe, etc.) [6][7][8], levures ou parasites [9,10].…”
Section: Définition Des Cellules Dendritiques Inflammatoiresunclassified
“…Différents groupes ont ainsi montré que, lors d'une inflammation, des monocytes injectés à des souris se différenciaient en cellules dendritiques inflammatoires [4,6,9,12,19]. L'utilisation de souris déficientes pour le récepteur de chimiokine CCR2, récepteur indispensable à la migration des monocytes, a permis d'aboutir à la même conclusion : l'absence de recrutement des monocytes sur le lieu d'inflammation compromet l'apparition des cellules dendritiques inflammatoires dont le nombre est alors sévèrement diminué [5,8,9,13,20]. Si l'on sait que la formation des cellules dendritiques inflammatoires n'est pas affectée par l'absence du ligand de Flt3 [19], on connaît mal en revanche les molécules impliquées dans la différenciation des monocytes en cellules dendritiques inflammatoires.…”
Section: Définition Des Cellules Dendritiques Inflammatoiresunclassified